Hand Anthropometry of Indonesian Young Adult Females - Angela Esmita Nidiaputri; Ardiyanto Ardiyanto (Perhimpunan Ergonomi Indonesia, 2017)
An anthropometric survey measuring 24 hand dimensions was conducted in 202 Indonesian young adult females. The samples consist of three different ethnic groups in Indonesia, including Bataknese, Javanese, and Sundanese. The means, standard deviations, and percentile values are summarized in tables. The means of the collected data between ethnic groups were compared. Also, comparisons between those of the collected data and other nationalities such Jordanian, Bangladeshis, Vietnamese, Hong Kong Chinese, Nigerian, and UK Resident are performed, using data from other published studies. The results showed many significant differences among ethnic groups as well as between the Indonesian and the other populations. The results of this study can be utilized as a consideration in the design or selection of the hand-operated products that are utilized by Indonesian young adult females.